Anna Julia Cooper: Standing at the Intersection of History and Hope - Shannon L Eickhoff (Educational Considerations, 2021)
Anna Julia Cooper transcended her historical place in time to become one of the most important examples of early resistance to intersectional oppression. Her seminal work, A Voice from the South (1892), articulates her feminine viewpoint on philosophy, social policies, religion, and the status of Black women’s education. Often using the language of the oppressor, Cooper’s acute wit and brilliant use of rhetorical devices allowed her to express herself in spheres of influence where she might otherwise have been silenced. Cooper’s steadfast dedication to racial uplift is illustrated through her life-long commitment to the education of Black women and their preparation to enter the fight for social justice. Her abiding devotion to her community can be seen through her work in the Colored Social Settlement Movement, Frelinghuysen University, and multiple other social organizations aimed at reaching the racially oppressed. This historical research analyzes the importance of Cooper’s work using Black Feminist Thought as a lens through which to view her work. It examines Cooper’s life, her dedication to Black women’s education and her tireless efforts to lift her community.
Keywords: Anna Julia Cooper; education; intersectionality; Black Feminist Thought; community uplift; racial and sexual equality